THE INDONESIA'S MARKET DIMENSIONS ON MONEY: Dimensi Pasar Uang Indonesia - Uliyatul Mu'awwanah; Ghoni Rizky Ridho Illah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The money market is a market or a meeting place for the supplying side (supplier) with the funds’ recipient (demand) that provides a system in which the granting of these funds will produce a profit in a certain period (short-term), generally no more than a year. Various instruments in the money market can be used as options by investors to suit their investment needs. There are also several indicators in the money market that can be used as a reference to determine the most liquid product to be considered. These indicators include information on market development paces such as interest rates and inflation. This article attempts to describe money market dimensions so that it is expected to provide an overview for the potential young investors among academics.